Abrupt tropical vegetation response to rapid climate changes - Hughen, K. A.; Eglinton, T. I.; Xu, L.; Makou, M. (Science, 2004)
Identifying leads and lags between high- and low-latitude abrupt climate shifts is needed to understand where and how such events were triggered. Vascular plant biomarkers preserved in Cariaco basin sediments reveal rapid vegetation changes in northern South America during the last deglaciation, 15,000 to 10,000 years ago. Comparing the biomarker records to climate proxies from the same sediment core provides a precise measure of the relative timing of changes in different regions. Abrupt deglacial climate shifts in tropical and high-latitude North Atlantic regions were synchronous, whereas changes in tropical vegetation consistently lagged climate shifts by several decades.
Hughen, Konrad AEglinton, Timothy IXu, LiMakou, MatthewengResearch Support, Non-U.S. Gov't2004/05/25 05:00Science. 2004 Jun 25;304(5679):1955-9. Epub 2004 May 20.